Integration of Local Wisdom in the Independent Curriculum: Strengthening Local Cultural Values and Traditions through Inter-Subject Learning in Madrasah of Riau Province - Rohani; Asmuri; Khusnul Nur Azizah (Attractive : Innovative Education Journal, 2026)
This study discusses the integration of local wisdom in the implementation of the Independent Curriculum in MTsN 2 and SMPN 2 Tembilahan Hulu as an effort to strengthen cultural values, character, and profiles of Pancasila Students. The main problems raised are the low structural recognition of local content and the limitations of teacher training in developing culture-based learning. The research used a qualitative method through in-depth interviews with Waka Curriculum and Riau Malay Culture (BMR) teachers to identify practices, challenges, and implementation strategies. The results show that the integration of local wisdom is carried out through three domains—intracurricular, cocurricular, and extracurricular—with a positive impact on learning motivation, cultural pride, and character formation of students. However, structural constraints and lack of resources are still the main obstacles. This research recommends strengthening culture-based education policies through formal recognition of local content, continuous teacher training, and collaboration between schools, customary institutions, and universities to ensure the sustainability of programs